After thought: Why not a prism? (Multilingual Margins: A journal of multilingualism from the periphery, 2023)
This paper is a reflective retrospective that suggests a new image of multilingualism. Instead of a "cat's cradle", the author proposes viewing multilingualism as a prism through which to view languages as different but non hirarchical and equal in value.